Do Blended Learning and Autonomous Learning Affect EFL Students’ Writing Achievement? Insight from Indonesia - Dwi Fita Heriyawati; Like Raskova Octaberlina; Daniel Ginting (Center of Language Development, Institut Agama Islam Negeri Madura, 2025)
Blended learning plays an important role in teaching writing and offers new prospects for enhancing autonomous learning in writing instruction for the Indonesian educational context. This study investigates the effectiveness of blended learning on students’ autonomous learning and writing achievement. This study employed a mixed-method research design, with sixty-six students from a private university in Malang, Indonesia, participating in the study, engaging in blended learning sessions comprising both online and face-to-face components. Findings indicate a significant interaction between blended learning and learners’ autonomy, positively influencing students’ writing proficiency. The study revealed a p-value of 0.029. The p-value is lower than the significance level of 0.05, which means that sig = 0.029 < 0.05. Based on the statistical computation’s outcomes, it can be inferred that the effect of blended learning depends on Autonomous Learning. This suggests that Autonomous Learning and blended learning both have an impact on students’ ability to write. Cooperatively, blended learning and autonomous learning have an interactive rather than additive impact on writing achievement. While the study underscores the potential benefits of blended learning, limitations include its focus on a specific student demographic and educational setting, potentially limiting generalizability. Implications suggest that educators consider integrating blended learning to enhance student engagement and writing skills.